Synthesis and Application of Acid Dyes Based on 3-(4-Aminophenyl)-5-benzylidene-2-substituted phenyl-3, 5-dihydroimidazol-4-one - Devang N. Wadia; Pravin M. Patel (E-Journal of Chemistry)
A series of eight novel heterocyclic based monoazo acid dyes were synthesized using various substituted imidazol-4-one as diazo component and coupled with various amino-napthol sulphonic acids. The resultant dyes were characterized using standard spectroscopic methods and then dyeing performance on wool fabric was assessed. Final results concluded that exhaustion (%E) of the dyes on wool fibers increased with decreasing pH of application and that fixation (%F) of the dyes on wool fibers increased with increasing pH of application and the highest total fixation efficiency was achieved at pH 5. Wash and light fastness properties of prepared dyes showed encouraging results.